PENGARUH MANAJEMEN SARANA PRASARANA DAN KOMPETENSI PEDAGOGIK GURU TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Inayah, Ina Nurul; Nugraha, Mulyawan Safwandi; Nasrudin, Endin (Jurnal Isema : Islamic Educational Management, 2023)
This study aims to determine the effect of management of facilities and infrastructure, teacher pedagogical competence, and quality of learning on students' interest in learning PAI at Unggulan Bina Insan Mulia 2 Senior High School Cirebon. The research was carried out with a quantitative approach. The population in this study were all students in class X and XI SMA Unggulan Bina Insan Mulia 2 Cirebon, while the sample for this study used a full sample, they are all students in class X and XI SMA Unggulan Bina Insan Mulia 2 Cirebon. The data analysis technique used is PLS-SEM. PLS-SEM is a structural equation model to develop or predict an existing theory. The equation model analyzed is the outer model, inner model and hypothesis testing. Based on calculations using SmartPLS 3.0 . The results showed that the management of facilities and infrastructure had an effect on student learning interest by 0.763 or 76.3%, teacher pedagogic competence had an effect on student learning interest by 0.312 or 31.2%, and the quality of learning had an effect on student learning interest by 0.335 or 33, 5%. The implications of the results of this study indicate that SMA Unggulan Bina Insan Mulia 2 Cirebon must improve the planning of educational facilities and infrastructure, because the completeness of educational facilities and infrastructure will assist teachers in organizing the learning process. The results of testing the hypothesis showed that there was a significant influence between the management of facilities and infrastructure on students' learning interest (t-statistic 3.554 and p values <0.05), there was a significant effect between teacher pedagogical competence on student learning interest (t statistic 3.934 and p values <0.05), and there is a significant influence between the quality of learning on students' learning interest (t statistic 4.161 and p values .0.05).